Understanding Sexual Harassment among Undergraduate Students’ in Higher Education Institution in Malaysia - Rapidah Omar Ali, Siti; Shafini Mohd Said, Nur; Amin Mat, Khalid; Mat Zali, Masliza; Aziz, Nurulnadwan (International Journal of Engineering and Technology, 2026)
Gender violence and sexual harassment in higher education have been studied and reported for the past decades. This study intended to identify the problem of sexual harassment in the academic background. Specifically, the objectives of this study tend to look at the awareness of sexual harassment among students, identify the effects of sexual harassment and examine the risk factors contributed to the occurrence. Questionnaires were distributed to 351 undergraduate students in a public university in East Coast Malaysia with the return rate of 78%. The findings revealed that 58.6% of the respondent have been harassed at least once and majority of them were female. The most common form of sexual harassment experience by the respondents was offensive behaviour. Majority of the respondents agreed that sexual harassment experienced affected their emotional greatly compared to education and productivity. Unprofessional learning environment shown to be the most risk factor associated to the incidents of sexual harassment.
Keywords: awareness; effect; higher education; sexual harassment; undergraduate student